2016
DOI: 10.1016/j.slsci.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Good daily habits during the early stages of life determine success throughout life

Abstract: This paper assesses hypothesis that sufficient sleep duration and proper circadian rhythms during the early stages of life are indispensable to a successful life. Successful life was defined according to the famous cohort studies of Mischel's and Dunedin. To assess the hypothesis, neuronal elements presumably affecting early daily habits and successful life are reviewed. The effect of sufficient sleep duration and proper circadian rhythms during early stages of life on the development of the prefrontal cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
0
1
0
1
Order By: Relevance
“…The correlation between stress and lifestyle habits has been confirmed in previous research [7]. For example, there are clear effects of lifestyle habits, such as dietary, exercise, or sleep habits, on health and lifespan [7] [8] [9]. It has also been indicated that there are various psychological factors that contribute to the occurrence of diseases related to lifestyle habits, such as heart disease, diabetes, or obesity, and that stress is a major psychological factor [10] [11].…”
Section: Introductionmentioning
confidence: 67%
“…The correlation between stress and lifestyle habits has been confirmed in previous research [7]. For example, there are clear effects of lifestyle habits, such as dietary, exercise, or sleep habits, on health and lifespan [7] [8] [9]. It has also been indicated that there are various psychological factors that contribute to the occurrence of diseases related to lifestyle habits, such as heart disease, diabetes, or obesity, and that stress is a major psychological factor [10] [11].…”
Section: Introductionmentioning
confidence: 67%
“…Узагальнюючи різносторонні погляди на природу звичок (Jun Kohyama, 2016; • яка гора перед нею: висока, мала, крута, полога, з рослинністю чи без. • що бачить навкруги: який пейзаж від початку сходу, яка пора року, яка погода в цей момент.…”
Section: методи та матеріалиunclassified